PESANTREN LITERATURE IN INDONESIAN LITERATURE CONSTELLATION - Muniroch, Sri (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
Pesantren literature challenges an issue of confession and acceptance in Indonesian literature. Questions on pesantren literature are concerned with the existence and literary quality of the works included in the category of pesantren literature. The important question is whether the works have literary uniqueness as specific genre that can be distinguished from other kinds of literary works. This article will not identify the literary quality of pesantren literature but tries to discuss the existence of pesantren literature among other Indonesian literary works. The discussion is expected to give an alternative perspective on the position of pesantren literature in the whole constellation of Indonesian literature.